Construct validity of Advanced Practice Role Delineation tool: A confirmatory factor analysis. Issue 5 (27th May 2022) - Jokiniemi, Krista; Tervo‐Heikkinen, Tarja; Peltokoski, Jaana; Mikkonen, Santtu
Abstract: Aim: To test the psychometric properties and latent structure of the modified Strong Model of Advanced Practice tool. Background: The Strong Model of Advanced Practice tool, developed in the United States in 1990s and its Australia modification, has been increasingly used to delineate nursing and advanced practice nursing roles. Few research‐driven efforts to develop and validate these tools have taken place. Design: Psychometric testing of the modified Strong Model of Advanced Practice tool. Methods: A confirmatory factor analysis was undertaken to examine the factors of the modified Strong Model of Advanced Practice tool and compare the model to the Australian Advanced Practice Role Delineation tool. The data were collected in September 2020. Results: The analysis of the data provided construct validity evidence of the underlying theoretical structures of the five‐factor modified Strong Model of Advanced Practice tool. The 45‐item modified Strong Model of Advanced Practice tool demonstrated satisfactory, slightly better psychometric properties and construct validity than the 40‐item Advanced Practice Role Delineation tool. Conclusions: Psychometric properties of the scale were evaluated and reported. Based on the statistical analysis, we suggest the use of the 45‐item modified Strong Model of Advanced Practice tool. Summary statement: What is already known about this topic? The Strong Model of Advanced Practice and its modifications have been increasingly used to delineate nursing and advanced practice nursing roles. Few research‐driven efforts to develop and validate these tools have taken place. What this paper adds? The analysis of the data provides construct validity evidence of the underlying theoretical structures of the five‐factor modified Strong Model of Advanced Practice tool. The tool demonstrates satisfactory, slightly better psychometric properties and construct validity than the 40‐item Advanced Practice Role Delineation tool. The implications of this paper: The validated modified Strong Model of Advanced Practice tool may be utilized to develop, standardize and delineate various nursing and advanced practice nursing roles within healthcare organizations. Based on statistical analysis, we recommend the use of a 45‐item Modified Strong Model of Advanced Practice tool.